La place des élèves des classes spécialisées dans l’école élémentaire : un analyseur de leur construction identitaire - Claire de Saint Martin (Éducation et Socialisation)
In primary school, children with disabilities can be admitted collectively to a specialised class, called "Class for School Inclusion" (CLIS). CLIS 1 are designed specifically for children with cognitive disabilities. Nevertheless, these children have to participate in regular class for specific lessons and share their school time between several educational spaces. How those affect the socialization of these children? Which identity construction do they allow? As part of a doctoral work, a collaborative research was conducted with teachers and children from three CLIS 1 by the establishment of an institutional socioclinical device. The results reveal the importance of educational spaces in the socialization of these children who develop an identity resistance to their status of "disabled" in the school space.